THE INFLUENCE OF FOOD QUALITY, SERVICE QUALITY , AND PRICE ON REPURCHASE INTENTIONS THROUGH CUSTOMER SATISFACTION AT PUTU MADE RESTAURANT JAKARTA - Verdy Suprianto; Himawan Brahmantyo; Rahmat Ingkadijaya (Jurnal Ekonomi, 2023)
This study is intended to examine the effect of food quality, service quality, and price on consumer repurchase intention through customer satisfaction visiting Putu Made restaurants in the Jakarta area. The data used in this research is primary data with a total sample of 111 respondents, namely consumers who are visiting the Putu Made Senayan City and Putu Made PIK Avenue restaurants. Then, the analysis technique used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. Data processing in research uses several applications, namely MS. Excel, and SmartPLS3. Based on the results of the SEM-PLS test, it is known that the variables of food quality, service quality, and price have a positive and significant direct effect on customer satisfaction. Then the variable customer satisfaction has a positive and significant effect on consumer repurchase intention. Then the variables of food quality, service quality, and price have a direct effect that is not significant on consumer repurchase intention. Then the variables of food quality, service quality, and price indirectly have a positive and significant effect on consumer repurchase intention through customer satisfaction. Suggestions for the Putu Made Jakarta restaurant in terms of food quality pay more attention to the level of maturity of the food served. If the level of maturity does not match customer needs, this will obviously cause dissatisfaction for customers which can ultimately affect their intention to repurchase, in terms of service quality the Putu Made Jakarta restaurant can increase employee empathy by providing training so that the Putu Made restaurant is able to have employees who can provide the best service, and from a price point of view the management of the Putu Made Jakarta restaurant can improve product pricing strategies by considering and taking into account the benefits that will be obtained by consumers.